Cantonese-Speaking Children Do Not Acquire Tone Perception before Tone Production—A Perceptual and Acoustic Study of Three-Year-Olds' Monosyllabic Tones - Wong, Puisan; Fu, Wing M.; Cheung, Eunice Y. L. (Frontiers in Psychology, 2017)
Models of phonological development assume that speech perception precedes speech production and that children acquire suprasegmental features earlier than segmental features. Studies of Chinese-speaking children challenge these assumptions. For example, Chinese-speaking children can produce tones before two-and-a-half years but are not able to discriminate the same tones until after six years of age. This study compared the perception and production of monosyllabic Cantonese tones directly in three-year-old children. Twenty children and their mothers identified Cantonese tones in a picture identification test and produced monosyllabic tones in a picture labeling task. To control for lexical biases on tone ratings, the mother- and child-productions were low-pass filtered to eliminate lexical information and were presented to five judges for tone classification. Detailed acoustic analysis was performed. Contrary to the view that children master lexical tones earlier than segmental phonemes, results showed that three-year-old children could not perceive or produce any Cantonese tone with adult-like proficiency and incorrect tone productions were acoustically different from criterion. In contrast to previous findings that Cantonese-speaking children mastered tone production before tone perception, we observed more accuracy during speech perception than production. Findings from Cantonese-speaking children challenge some of the established tenets in theories of phonological development that have been tested mostly with native English speakers.